Practicability analysis and economics of using different substrates for oyster mushroom Pleurotus djmore and Pleurotus sajor-caju by woman self help group in Uttarkashi district of Uttarakhand - SINGH, S P; SACHAN, V K; NAUTYAL, PANKAJ; TIWARI, R K; JOSHI, H C (The Indian Journal of Agricultural Sciences, 2026)
Pleurotus djmore and Pleurotus sajor-caju were cultivated on different plant substrates in District Uttarkashi, Uttarakhand. P. djmore fruits well at 20 - 300C and P. sajor-caju at 18 -280C. Plant wastes or substrates, viz. wheat straw, hybrid Napier, maize cob shell, finger millet waste, blackgram waste, lentil kernel, and chopped mustard straw were used as alternative substrates for the cultivation of P. djmore and P. sajor-caju. The biological efficiency (BE) obtained from each substrate was more than 90%. The highest yields of P. djmore (1180 g/500 g dry substrate, BE 118%) and P. sajorcaju (1020 g/500g dry substrate, BE 102%) were obtained on wheat straw substrate. Others also proved to be good substrates for mushroom cultivation. Economic profitability analysis showed that Pleurotus mushroom cultivation is income-generation entrepreneurship that woman self help group and unemployed youth can easily adopt. Mean cost benefit ratio of 1:4.6, 1:3.7 and 1:2.2 were obtained at 100%, 80% and 60% of experimental yields.